Development of Multimodal Interfaces: Active Listening and Synchrony Second COST 2102 International Training School, Dublin, Ireland, March 23-27, 2009, Revised Selected Papers - Esposito, Anna.; Campbell, Nick.; Vogel, Carl.; Hussain, Amir.; Nijholt, Anton; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The themes of the papers presented in this book emphasize theoretical and practical issues for modelling human-machine interaction, ranging from the attempt in describing (3z(Bthe spacing and orientation in co-present interaction(3y (Bto the effort for developing multimodal interfaces, collecting and analysing interaction data and emergent behaviour as well as analysing the use of nonverbal and pragmatic elements of exchanges, implementing discourse control and virtual agents and using active listening in computer speech processing.s
Spacing and Orientation in Co-present Interaction -- Group Cohesion, Cooperation and Synchrony in a Social Model of Language Evolution -- Pointing Gestures and Synchronous Communication Management -- How an Agent Can Detect and Use Synchrony Parameter of Its Own Interaction with a Human? -- Accessible Speech-Based and Multimodal Media Center Interface for Users with Physical Disabilities -- A Controller-Based Animation System for Synchronizing and Realizing Human-Like Conversational Behaviors -- Generating Simple Conversations -- Media Differences in Communication -- Towards Influencing of the Conversational Agent Mental State in the Task of Active Listening -- Integrating Emotions in the TRIPLE ECA Model -- Manipulating Stress and Cognitive Load in Conversational Interactions with a Multimodal System for Crisis Management Support -- Sentic Computing: Exploitation of Common Sense for the Development of Emotion-Sensitive Systems -- Face-to-Face Interaction and the KTH Cooking Show -- Affect Listeners: Acquisition of Affective States by Means of Conversational Systems -- Nonverbal Synchrony or Random Coincidence? How to Tell the Difference -- Biometric Database Acquisition Close to (3z(BReal World(3y (BConditions -- Optimizing Phonetic Encoding for Viennese Unit Selection Speech Synthesis -- Advances on the Use of the Foreign Language Recognizer -- Challenges in Speech Processing of Slavic Languages (Case Studies in Speech Recognition of Czech and Slovak) -- Multiple Feature Extraction and Hierarchical Classifiers for Emotions Recognition -- Emotional Vocal Expressions Recognition Using the COST 2102 Italian Database of Emotional Speech -- Microintonation Analysis of Emotional Speech -- Speech Emotion Modification Using a Cepstral Vocoder -- Analysis of Emotional Voice Using Electroglottogram-Based Temporal Measures of Vocal Fold Opening -- Effects of Smiling on Articulation: Lips, Larynx and Acoustics -- Neural Basis of Emotion Regulation -- Automatic Meeting Participant Role Detection by Dialogue Patterns -- Linguistic and Non-verbal Cues for the Induction of Silent Feedback -- Audiovisual Tools for Phonetic and Articulatory Visualization in Computer-Aided Pronunciation Training -- Gesture Duration and Articulator Velocity in Plosive-Vowel-Transitions -- Stereo Presentation and Binaural Localization in a Memory Game for the Visually Impaired -- Pathological Voice Analysis and Classification Based on Empirical Mode Decomposition -- Disfluencies and the Perspective of Prosodic Fluency -- Subjective Tests and Automatic Sentence Modality Recognition with Recordings of Speech Impaired Children -- The New Italian Audio and Video Emotional Database -- Spoken Dialogue in Virtual Worlds.s
Keywords: Computer science; Information systems; Multimedia systems; Computer graphics; Computer vision; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Multimedia Information Systems; Computers and Society; Image Processing and Computer Vision; Computer Graphics